Programa de capacitação da SEED/PR (2011-2014): aspectos políticos e ideológicos na formação continuada de professores - Zanella, Andreia Migon (2015)
This research analyzed the Teachers Training Program of basic education in state public schools, in the modalities Pedagogical training and Teacher training of the Department of education in Dois Vizinhos, Francisco Beltrão and Pato Branco/PR. The modalities were carried between 2011 and 2014, by SEED/PR, the objective was identified the principles that base in relation with the political and modern project. The finished was in 2015, when was developed process analysis of the historical constitution program (1995-2010); official documents that orient the program: State Education plan(2005), Resolutions 1457/2004;2007/2005, the materials were available for Pedagogical training and Teacher training (2011-2014); Government s plan (2011-2014), target plan (2011- 2012) interviews with two representatives of the SEED/PR, three coordinators of the basic education, three coordinatiors of the continued formation of the Department of education in Dois Vizinhos, Francisco Beltrão and Pato Branco/PR, three principals, four pedagogues and twenty-one teachers of the Department of Education in Francisco Beltrão; and the reading of the area s bibliography, highlighting research able to provide current data and relevant about the subject (Chimentão, 2010; Jost, 2010; Nadal, 2007; Saldanha, 2010). The information collected were analyzed from the Presumptions of the historical materialism (Gramsci, 2001; Gentili, 1998; Kosik, 1976; Marx, 2010; Neves, 2005; Vázques, 1977) option theoretical-methodological that possibility a critical reflection about teacher s continued formation considered in its totality relations and contradictions, discussed in the form how is elaborated, organized and performed the offer of the SEED/PR . The result shows that theoretical and methodological foundations of the training program sustain in continuity for the offer in the perspective of the practical rationality in prevalence of the continued formation reduced the training for technical knowledge with the goal of the increasing indices related school performance and reduction the dropout rates and reproach, untied of the social background that the school, students and teachers and the solid formation in Scientific Knowledge This way, the training program stays developing for perspective of the practical rationality, but differentiate the past periods, because of the strategies increased in prescription, intervention in the state control in the results of the learning process and it is articulated presumptions neoliberal ideological whose goals are effectiveness and efficiency. The program doesn t impact significantly for teachers practices and the process emancipation of the teachers and students. It is process of the formation that don t relate the needs formative of the professional group and mainly, for ignore the all of the relations that determined the development of the teachers practices. This research points the principles for a counterhegemonic formation project in the critical perspective, like is necessary to grant deepening theoretical-methodological in the Teacher s continued formation that interfere in formation of the professionals that have concepts acquired in the perspective of the articulation of the object (education) with all of the elements (historical, political, economic, philosophical, ideological, scientific, social) that determine.